Manfaat Media Modern dalam Membangun Dakwah Efektif - Erwan Efendi; Muhammad Abdillah Habibi; Rahma Dewi; Tri Fia Akmala (VISA: Journal of Vision and Ideas, 2024)
In fact, da'wah is an obligation for all mankind, in the form of a message of invitation from negative to positive actions to achieve the truth. In this era, conveying a da'wah message must be effective. Nowadays, da'i, khatib, ustadz, or ustazah may use the media or other methods of da'wah as additional tools to help their da'wah efforts. As a result, various new media are used to help implement da'wah, showing the importance of the internet as a tool for expanding and building successful da'wah today. Therefore, in this journal article the author discusses the benefits of modern media in building effective da'wah.